A Study of Indian Environmental Movement: A Social Aspect: Determinant Factors of Success and Failure in Indian Environmental Movements (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The study of environmental movements has become one of the important discourses in academics and it has a number of aspects. This article investigates the determinant factors of success and failure of environmental movements in India based on a comparative analysis of the colonial regime, post-independence regime, and the more recent era of liberalization. The movements during the 1960s and 1970s were suppressed by the democratic state, because they did not have this kind of support. The factors that were responsible for the success of the environmental movements in the late 1970s and 1980s have not produced as much success in the more recent era of liberalization.